KAJIAN BIOKOMPLEK TRICO-G DAN INOKULASI RHIZOBIUM PADA HASIL TANAMAN KEDELAI (Glycine max (L.) MERRILL) - Jumini Jumini; Rita Hayati (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2010)
ABSTRACT Study of Biokomplek Trico-G and Inoculation of Rhizobium on soybean yield has been conducted. The aim of research was to evaluate concentration of Biokomplek Trico-G and Rhizobium inoculation on yield. The experiment used a randomized complete block design 4x2 with 3 replicates. Factors evaluated were concentration of Biokomplek Trico-G, consisted of 4 levels, that is: 0, 5, 10 and 15 g/L water and Rhizobium inoculation, consisted of 2 levels, that is without inoculation and inoculation with ex-soybean soil. Results showed that the concentration of Biokomplek Trico-G had a highly significant effect on dry weight seed per crop and dry weight seed per hectare and had a significant effect on seed diameter. The best result was concentration of Biokomplek Trico-G at 10 g/L water. Inoculation of Rhizobium had a highly significant effect on number of productive branches and a significant effect on number of fine pods per crop but insignificant effect on seed diameter, dry weight of seed per crop and dry weight of seed per hectare. The best result was inoculation with ex-soybean soil.